Beneficial modification of functional renal parameters in 5/6 nephrectomized rats by nutraceutical. In view of a kidney-protective intervention - Harada, M.; Sweed, H.; Catanzaro, et al., R. (Acta Biomedica Atenei Parmensis, 2012)
The objective of this study is to ascertain the potential beneficial effects of a novel phytoterapeutic formula (DTS, Kyotsu Jigyo, Japan) on renal function and morphological structure in 5/6 nephrectomized rats. Male Spraque-Dawley rats, 240-280 g, were divided into sham control (Group A) and nephrectomized (Group B and Group C) groups. The 5/6 nephrectomy was performed by removal of the right kidney and 2/3 ligation of left renal artery. After surgery, the animals were kept in individual cage for 6 weeks. Rats in Group A and Group B were fed with a normal protein diet only while those in Group C were fed normal protein diet added with DTS (10 mg/rat/day). The DTS supplementation was started a day after surgery. After 5 weeks, all rats were subjected to renal function study and then their left kidneys were isolated for morphological study. There were no significant differences in body weight, blood pressure, and heart rate among groups. DTS supplementation significantly increased (p < 0.05) plasma creatinine concentration, glomerular filtration rate, effective renal plasma flow, and urine flow rate in nephrectomized rats when compared to sham control (Group A) and untreated nephrectomized (Group B) controls. In contrast, plasma urea concentration and morphological structure were not significantly modified by DTS supplementation in nephrectomized animals. These data suggest that feeding with a normal protein diet and DTS supplementation improves renal function without any morphological effect in 5/6 nephrectomized rats if not a slight preservation.